2013
DOI: 10.3346/jkms.2013.28.10.1552
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hemorrhagic Fever with Renal Syndrome in Korea, 2001-2010

Abstract: This study describes the epidemiology of hemorrhagic fever with renal syndrome (HFRS) in the past 10 yr (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) in Korea. During this period, a total of 3,953 HFRS patients and an average prevalence rate of 0.81 per 100,000 population were recorded, with a total of 40 fatal cases, corresponding to a case fatality rate of 1.01%. More HFRS cases were found in men than in women (57% vs 43%), and a higher prevalence rate of HFRS was observed in patients older th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
5
18
0
Order By: Relevance
“…In this study, the majority of the HFRS cases were reported in the last quarter of the calendar year (October, November, and December). Presumably, the higher incidence of HFRS in these months can be attributed to the higher numbers of hantavirus-infected rodents in the ROK during this period [16]. Here, we found that a significantly (P < 0.01) higher proportion of HFRSpositive rodents was collected in Jeju during May (85.7%) and October (50%).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In this study, the majority of the HFRS cases were reported in the last quarter of the calendar year (October, November, and December). Presumably, the higher incidence of HFRS in these months can be attributed to the higher numbers of hantavirus-infected rodents in the ROK during this period [16]. Here, we found that a significantly (P < 0.01) higher proportion of HFRSpositive rodents was collected in Jeju during May (85.7%) and October (50%).…”
Section: Discussionsupporting
confidence: 44%
“…Additionally, serological results were obtained for 5 (11%) of the A. agrarius serum samples collected from Jeju. Interestingly, until 2013, only a single human HFRS case was documented from Jeju Island, amongst a total of 3,953 HFRS cases reported over almost a decade in the ROK [16,18]. Another report, published in 2017, referenced five human HFRS cases from Jeju over a period from 2001 to 10 season variation suggests that this region may be at risk for a viral outbreak in the future.…”
Section: Discussionmentioning
confidence: 99%
“…agrarius was much lower for Gangwon province, these data suggest that Gyeonggi province poses significantly higher HFRS health risks than Gangwon province [ 8 , 9 , 14 , 15 ]. To support this, the incidence of HFRS patients in Gangwon province was lower than that in Gyeonggi province, demonstrating a correlation between rodent seroprevalence and human disease data [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have investigated the epidemiology of HFRS in Korea, which showed a higher incidence of HFRS in Yeoncheon than in other regions. A study of HFRS epidemiology from 1996 to 1998 reported that the incidence of HFRS in Yeoncheon was 2.3-6.3 per 100,000 individuals, which was much higher than the national average (0.81 per 100,000) [ 13 16 ]. In a nationwide study of HFRS epidemiology in Korea that was conducted from 2001 to 2010, 17.2% (678/3,953) of HFRS cases occurred in the Gyeonggi province, which includes Yeoncheon, and this province showed a higher incidence than any other region in Korea [ 16 ].…”
Section: Introductionmentioning
confidence: 99%